Extracellular vesicle mimetics as delivery vehicles for oligonucleotide-based therapeutics and plasmid DNA - Anastasiya Oshchepkova; Ivan Chernikov; Svetlana Miroshnichenko; Olga Patutina; Oleg Markov; Innokenty Savin; Yaroslav Staroseletz; Mariya Meschaninova; Pavel Puchkov; Sergey Zhukov; Maxim Kupryushkin; Mikhail Maslov; et al. (Frontiers in Bioengineering and Biotechnology)
IntroductionSmall membrane particles called extracellular vesicles (EVs) transport biologically active cargo between cells, providing intercellular communication. The clinical application of EVs is limited due to the lack of scalable and cost-effective approaches for their production and purification, as well as effective loading strategies.MethodsHere we used EV mimetics produced by cell treatment with the actin-destabilizing agent cytochalasin B as an alternative to EVs for the delivery of therapeutic nucleic acids.ResultsCytochalasin-B-inducible nanovesicles (CINVs) delivered a fully modified N-(methanesulfonyl)- or mesyl (µ-) antisense oligonucleotide to B16 melanoma cells, selectively decreasing the level of target microRNA-21 with effectiveness comparable to that observed upon Lipofectamine 2000-mediated delivery. The efficiency of the CINV-mediated delivery of plasmid DNA encoding EGFP varied depending on the type of recipient cells. Surprisingly, under experimental conditions, CINVs were unable to deliver both modified and natural short RNA duplexes—small interfering RNA and immunostimulatory RNA—probably due to their poor loading into CINVs.DiscussionCINVs demonstrated unique properties for the delivery of therapeutic nucleic acids, especially for antisense oligonucleotide-based therapy.